Environmental impacts shape the density-size relationship of benthic macroinvertebrates in Amazonian streams (Serra dos Carajás, Pará, Brazil) - Maria Eduarda Cabral Liberal; Camila Pinto Leão; Jaqueline Silva de Oliveira; Francisco Valente-Neto; Bruno Spacek Godoy (Acta Limnologica Brasiliensia)
Abstract: Aim Streams are small lotic ecosystems essential for aquatic biodiversity and nutrient cycling. However, they are highly susceptible to anthropogenic pressures, such as the replacement of native vegetation by plantations, which can affect aquatic communities—especially benthic macroinvertebrates, due to their sensitivity to environmental changes. While most studies rely on taxonomic metrics, there is growing evidence that changes in riparian vegetation can alter size-density relationships. We hypothesized that impacted streams would exhibit shifts in macroinvertebrate size-density patterns reflecting environmental degradation. Methods We sampled 15 Amazonian streams in the Serra dos Carajás region, southeastern Pará State, Brazil, an area influenced by agriculture, livestock, and mining. Sampling occurred during the dry season across two campaigns. Macroinvertebrates were collected using a kick-net, and physical-chemical variables were measured with a multiparameter probe and turbidimeter. Environmental variables were analyzed using principal component analysis, and size-density relationships were evaluated with a second-order polynomial model. Results Agricultural impact altered size-density relationships. Impacted sites showed reduced macroinvertebrate density across all size classes and a concentration of individuals in intermediate sizes. These changes suggest a simplification of trophic networks and decreased energy transfer efficiency. Conclusions Anthropogenic impacts significantly alter aquatic communities in Amazonian streams. The study demonstrates that agricultural activity reduces macroinvertebrate density in all size classes, signaling a widespread collapse of trophic networks. These findings highlight the vulnerability of Amazonian streams to human disturbances and underscore the importance of monitoring size-density relationships as indicators of ecosystem integrity.